Alfred Wierusz-Kowalski: Political Struggle and Metaphor - (:unkn) unknown (My University, 2016)
This thesis examines the role that political metaphor plays in the artwork of Alfred Wierusz-Kowalski (1849 – 1915), a Polish painter of the late nineteenth and early twentieth centuries. He studied in Poland and later at the Munich Academy of Fine Arts, where he was known for paintings of the everyday lives of rural, Polish people. Later in his career, he delved into historical and romantic subjects, most notably the Cossacks, an East Slavic, semi-military people with deep roots in Poland. In the eighteenth century, Poland was conquered and partitioned by the imperial powers of Russia, Prussia, and Austria. During Wierusz-Kowalski’s lifetime the Polish people were under constant duress, a state reflected in many of his paintings. His works often suggested the struggles of Polish people in those lands that became Russian territory. Such paintings illustrated the vast class divide that existed between the gentry and the peasants, but also spoke to a deep sense of national pride among the Polish people. Subtle details of Wierusz-Kowalski’s paintings of Poland reveal his critique of the social and political issues that confronted the nation.
Keywords: Alfred Wierusz-Kowalski; Returning Home at Sunset; Russian Winter Scene